Capacity Constraints on Progressing of National Highway Projects in India - Kishore Kumar, M.; Hanumantha Rao, Ch. (Prabandhan: Indian Journal of Management, 2011)
AD Narain (2010) states that the ambitious target in the highway sector of building 20 km of road per day is no doubt a very laudable aim, but to achieve the same, a number of ingredients leading to the successful completion of such projects needs a thorough discussion. On one side, it is well accepted that capacity constraints exist across the board, encompassing Employers, Contractors and Consultants. Whereas, there is a continuous effort to address these shortcomings through skill upgradation by training, obtaining personnel from outside the country, partnering with International Companies as Joint Venture/Associations, etc. Still, there is considerable gap between demand and supply. This paper delves at length on the issues concerning capacity constraints and suggests measures for removal of these impediments for smooth progressing of works on various ongoing highway development programmes.